SURVIVAL ASPECTS IN FIRST THEY KILLED MY FATHER (2017): INSIGHTS FROM GONZALES' THEORY - Mahendra, I Gede Danu; Syamsuar, Fauzi; Nawakwulan, Lyla (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
The movie First They Killed My Father (2017) portrays the harrowing experiences of a five-year-old girl, Loung Ung, who survived the Khmer Rouge regime's atrocities. This research analyzes Loung Ung's survival behaviors using Laurence Gonzales' survival theory from his book Deep Survival: Who Lives, Who Dies, and Why. Gonzales identifies key aspects of survival, including perception and cognition, acceptance, mental toughness and resilience, improvisation and adaptability, and hope and faith. Employing a descriptive qualitative method, this study examines specific scenes from the movie to highlight how Loung's behavior aligns with these survival aspects. The findings reveal that Loung's survival is significantly influenced by her acceptance of reality, emotional resilience, and ability to adapt to rapidly changing and dangerous circumstances. For instance, Loung demonstrates acceptance when she quickly adapts to the new norms imposed by the regime. Her mental toughness and resilience are evident as she maintains hope and determination despite immense loss and trauma. Furthermore, her improvisation and adaptability are showcased in her resourceful strategies to survive. This research contributes to the understanding of human resilience and the psychological mechanisms that enable individuals to survive extreme conditions.